Cesarean delivery on maternal request in Israel: Maternity department policies and obstetricians' perspectives. (November 2022) - Hirsh-Yechezkel, Galit; Glasser, Saralee; Farhi, Adel; Levitan, Gila; Shachar, Yael; Zaslavsky-Paltiel, Inna; Boyko, Valentina; Ezra, Yossef; Lerner-Geva, Liat
Objective: This study aimed to describe Israeli maternity departments' policies regarding cesarean delivery on maternal request, and factors associated with obstetricians' support for cesarean delivery on maternal request in specific scenarios. Methods: This multicenter cross-sectional study included 22 maternity department directors and 222 obstetricians from the majority of Israeli hospitals. Directors were interviewed and completed a questionnaire about their department's cesarean delivery on maternal request policy, and obstetricians responded to a survey presenting case scenarios in which women requested cesarean delivery on maternal request. The scenarios represented profiles referring to the following factors: maternal age, poor obstetric history, pregnancy complications, and psychological problems. The survey also included the obstetricians' socio-demographic information and questions about other issues associated with cesarean delivery on maternal request. The main outcome measures were department policies regarding cesarean delivery on maternal request and obstetricians' support for cesarean delivery on maternal request in specific cases. Results: Policies were divided between allowing and prohibiting cesarean delivery on maternal request (n = 10 and 12, respectively), and varied regarding issues such as informed consent and pre-surgery consultation. Most of the obstetricians (96.5%) did not support cesarean delivery on maternal request in the "reference scenario" describing a young woman with no obstetric complications. Additional factors increased the rate of support. Support was greater among obstetricians aged > 45 (odds ratio = 2.11; 95% confidence intervals 1.33–3.36) and lower among females (odds ratio = 0.58; 95% confidence intervals 0.39–0.86). Obstetricians whose department policy was less likely to allow cesarean delivery on maternal request reported lower rates of support for cesarean delivery on maternal request in most cases. Conclusion: Policies and obstetricians' support for cesarean delivery on maternal request vary broadly depending on clinical profiles and physician characteristics. Department policy has an impact on obstetricians' support for cesarean delivery on maternal request. Health policy will benefit from a framework in which the organizations, physicians, and patients are consulted.